2015
DOI: 10.3389/fpls.2015.01012
|View full text |Cite
|
Sign up to set email alerts
|

From Genetics to Functional Genomics: Improvement in Drought Signaling and Tolerance in Wheat

Abstract: Drought being a yield limiting factor has become a major threat to international food security. It is a complex trait and drought tolerance response is carried out by various genes, transcription factors (TFs), microRNAs (miRNAs), hormones, proteins, co-factors, ions, and metabolites. This complexity has limited the development of wheat cultivars for drought tolerance by classical breeding. However, attempts have been made to fill the lost genetic diversity by crossing wheat with wild wheat relatives. In recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 82 publications
0
94
0
3
Order By: Relevance
“…Effective dissection of drought-adaptive mechanisms at the cellular and molecular levels requires the integration of sophisticated functional genomics approaches, such as transcriptomics, metabolomics, and proteomics (15,37). Several studies were conducted in an attempt to unravel molecular mechanisms of adaptation to drought in DIC by comparing the transcriptome and metabolome profiles of genotypes contrasting in tolerance to drought stress [drought-resistant (R) versus drought-susceptible (S)], selected after screening of DIC populations from Israel and Turkey (31,65,66,104).…”
Section: Molecular Mechanisms For Adaptation To Drought In Dicmentioning
confidence: 99%
“…Effective dissection of drought-adaptive mechanisms at the cellular and molecular levels requires the integration of sophisticated functional genomics approaches, such as transcriptomics, metabolomics, and proteomics (15,37). Several studies were conducted in an attempt to unravel molecular mechanisms of adaptation to drought in DIC by comparing the transcriptome and metabolome profiles of genotypes contrasting in tolerance to drought stress [drought-resistant (R) versus drought-susceptible (S)], selected after screening of DIC populations from Israel and Turkey (31,65,66,104).…”
Section: Molecular Mechanisms For Adaptation To Drought In Dicmentioning
confidence: 99%
“…There are reviews focusing on drought tolerance traits in wheat and the underlying molecular mechanisms (for example, Budak et al 2015, Sheoran et al 2016, Mohammadi 2018. Here, we do not intend to be repetitive and to exhaustively review these traits and their molecular basis.…”
Section: Traits and Their Molecular Basis Potentially Associated Withmentioning
confidence: 99%
“…In fact, the negative effects of drought could be overcome by the identification and use of drought-tolerant varieties (Van Oosten et al, 2016). Given this solution, the dissection of molecular mechanisms that underlie adaptive traits represents one approach to understanding stress tolerance in plants (Budak et al, 2015;Liu et al, 2017;Arriagada et al, 2017). For example, Merchuk-Ovnat et al (2016) showed that the introgression of QTLs on chromosomes 1B and 2B of T. turgidum into T. aestivum can enhance drought tolerance in domesticated wheat.…”
Section: Introductionmentioning
confidence: 99%